Low biodegradability of dissolved organic matter from Southeast Asian peat-draining rivers - Nichols, Robert S. (2021)
Southeast Asia's extensive tropical peatlands account for a significant proportion of the global riverine dissolved organic carbon (DOC) flux to the ocean. Peat-derived DOC is rich in polyphenolic compounds, the microbial degradation of which is thought to rely on extracellular phenol oxidases. Despite substantial interest in the biogeochemical fate of terrigenous DOC (tDOC), few studies have quantified phenol oxidase activity in aquatic environments, and microbial remineralization rates of tDOC have never been measured in Southeast Asia. Here, we assess the potential for using phenol oxidase assays as a proxy for tDOC biodegradation across peat-draining rivers and the coastal waters of Sarawak, Borneo, and report experimental measurements of microbial tDOC remineralization rates from this region. We first show that phenol oxidase assays in aquatic samples are problematic because of the rapid, pH-dependent autoxidation of the assay substrate. Our field measurements of phenol oxidase activity detected only substrate autoxidation, suggesting that real phenol oxidase activity was low or absent. Second, we report that peatland tDOC, collected from one of the few remaining intact peatlands on Borneo, showed at most very limited biodegradation (0%–6% loss of DOC, and 0%–12% loss of colored dissolved organic matter) during several 56-day incubation experiments at an in situ temperature of ∼30°C, even when diluted with seawater or amended with nutrients. Our results suggest that direct microbial respiration is perhaps not a major pathway for peatland tDOC remineralization in Southeast Asia and that photo-oxidation is more likely to control the fate of this carbon.